Fiscal Reforms That Work. (Economic Issues; Economic Issues ;, 1997)
Reducing the budget deficit is not easy. Keynesian theory suggests thatlowering government expenditures and raising revenues can lead to afalloff in economic activity. This paper argues the neoclassical approach - that a firm and credible reduction in expenditures, by engendering confidence that taxes will be less burdensome in the future,may lead to lower interest rates, boost consumption, and increaseinvestment spending.